bowel, an odd-skipped homolog, functions in the terminal pathway during Drosophila embryogenesis. - Wang, L (1996)
The terminal genes of Drosophila specify non-segmented regions of the larval body that are derived from the anterior and posterior regions of the early embryo. Terminal class genes include both maternal-effect loci (typified by the receptor tyrosine kinase torso) that encode components of a signal transduction cascade and zygotic genes (e.g. tailless and huckebein) that are transcribed at the poles of the embryo in response to the local activation of the pathway. We have characterized a zygotic gene, bowel, that was identified as a zinc finger homolog of the pair-rule segmentation gene odd-skipped. bowel transcripts are initially expressed at both poles of the blastoderm embryo and in a single cephalic stripe. This pattern depends upon torso and tailless activity, but is not affected in huckebein mutants. We isolated and sequenced five mutations that affect the bowel protein, including a nonsense mutation upstream of the zinc fingers and a missense mutation in a putative zinc-chelating residue. bowel mutants die as late embryos with defects in terminal derivatives including the hindgut and proventriculus. Our results indicate that the developmental roles of odd-skipped and bowel have diverged substantially, and that bowel represents a new member of the terminal hierarchy that acts downstream of tailless and mediates a subset of tailless functions in the posterior of the embryo.